The effect of dietary methionine levels on growth, feed conversion and protein retention efficiency of Nile Tilapia (Oreochromis niloticus) fingerlings - FOUZI A. MOHAMMED; Ramzy Yousif; FATIMA M. HILAL; RAHMA A. ADAM; TAMNY K. AHMED (Smujo International, 2020)
Abstract. Mohammed FA, Yousif RA, Hilal FM, Adam RA, Ahmed TK. 2020. The effect of dietary methionine levels on growth, feed conversion and protein retention efficiency of Nile Tilapia (Oreochromis niloticus) fingerlings. Nusantara Bioscience 12: 21-27. A 49 days feeding trial was conducted to evaluate growth, feed utilization and body composition of Nile tilapia Oreochromis niloticus (4.30±0.01 g), fed five isonitrogenous (32 g 100 g-1 crude protein) and isoenergetic (14.51 kJ g-1 Gross energy) practical diets and five levels of methionine supplementation (0.5, 1, 1.5, 2 and 2.5 g 100 g-1). The experimental design was completely randomized with five treatments and three replicates. Fish were stocked in triplicate groups of 20 fish held in 70 L flow-through tanks (water volume 55 L) and fed twice daily (08:00 am and 04:30 pm) to apparent satiation. When absolute weight gain (AWG; g fish-1), feed conversion ratio, protein deposition (g fish-1) and protein retention efficiency (%) data were subjected to second-degree polynomial regression analysis 95% of the plateau of the above parameters was achieved at dietary methionine concentrations between 1.4-1.5 g 100 g-1 dry diet or 0.09-0.10 g methionine kJ-1 GE. Corresponding to 4.4-4.7 g 100 g-1 of the dietary protein. Based on these results, dietary methionine requirement for Nile tilapia Oreochromis niloticus is recommended 1.4-1.5 g 100 g-1 diet.